2006
DOI: 10.1111/j.1399-5618.2006.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Affective instability as rapid cycling: theoretical and clinical implications for borderline personality and bipolar spectrum disorders

Abstract: Objectives:  The Diagnostic and Statistical Manual of Mental Disorders guidelines provide only a partial solution to the nosology and treatment of bipolar disorder in that disorders with common symptoms and biological correlates may be categorized separately because of superficial differences related to behavior, life history, and temperament. The relationship is explored between extremely rapid switching forms of bipolar disorder, in which manic and depressive symptoms are either mixed or switch rapidly, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(105 citation statements)
references
References 88 publications
6
97
0
2
Order By: Relevance
“…Operationalizing AI has proved difficult (MacKinnon and Pies, 2006), although statistical 75 modelling and methods based on experience sampling applied in the short term (Ebner- , Ebner-Priemer et al, 2007a and longer term (Bonsall et al, 2012a) 77 have been suggested.…”
mentioning
confidence: 99%
“…Operationalizing AI has proved difficult (MacKinnon and Pies, 2006), although statistical 75 modelling and methods based on experience sampling applied in the short term (Ebner- , Ebner-Priemer et al, 2007a and longer term (Bonsall et al, 2012a) 77 have been suggested.…”
mentioning
confidence: 99%
“…With the publication of the DSM-V soon approaching, arguments have been advanced for broadening the bipolar spectrum even further, adding recurrent depression without hypomania (Benazzi, 2002), irritability (Benazzi & Akiskal, 2005); agitated depression (Akiskal et al, 2000;Benazzi, Koukopoulos, & Akiskal, 2004) and borderline personality disorder (Mackinnon & Pies, 2006;Smith, Muir, & Blackwood, 2005). Even without a further loosening of diagnostic criteria, Akiskal et al (2000) estimates that half of those now carrying diagnoses of major depression will be recast as bipolar.…”
Section: Bipolarmentioning
confidence: 99%
“…Others develop unipolar depression [29], anti-social personality disorder with affective symptoms [30] and borderline personality disorder [31]. Thus, children who meet the criteria for SMD Table I.…”
Section: Course and Outcomementioning
confidence: 99%